A novel mechanical metamaterial with tailorable vibration damping and compression behavior - Tan, Eugene Xing Hao (Nanyang Technological University, 2024)
Mechanical Metamaterials are a novel category of engineered materials that feature extraordinary mechanical properties not commonly found in traditional materials. These specially engineered materials do not derive their unique properties from the composition of the base material, but rather from the internal geometry of the metamaterial itself. In this report, a novel second-order hierarchical Mechanical Metamaterial, constructed from a conventional Octet-truss lattice with 3D Chiral lattice structure embedded within the trusses, is proposed as a space filling lattice, which possesses both superior mechanical properties and tailorable passive damping characterises. The addition of the 3D Chiral lattices would introduce laterally self-rotating elements into the Octet-truss lattice, which would disrupt the transmission of vibrations through the lattice by transforming the longitudinal waves to lateral ones, achieving a vibration damping effect. The efficacies of the mechanical properties and the frequency response characterizes of the proposed novel Mechanical Metamaterial will be evaluated and analyzed through the Finite Element Method as well as through experimental means. Laser Powder Bed Fusion Additive Manufacturing was employed to fabricate the various configuration of novel Mechanical Metamaterials evaluated to validate the results obtained from the Finite Element Analysis.